Morning Girl - Dorris, Michael A. 1945-1997 (Hyperion Paperbacks for Children, 1994)
Morning Girl, who loves the day, and her younger brother Star Boy, who loves the night, take turns describing their life on an island in pre-Columbian America; in Morning Girl's last narrative, she witnesses the arrival of the first Europeans to her world
Keywords: Arawak Indians / Juvenile fiction; Arawak Indians / Fiction; Indians of the West Indies / Fiction; Brothers and sisters / Fiction; Indigenes Volk; Geschwister; Verschiedenheit; Toleranz; America / Discovery and exploration / Spanish / Fiction; Amerika; Bahamas; Kinderbuch